2019
DOI: 10.1097/pgp.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumors of the Fallopian Tube: Report of a Case Series and Review of the Literature

Abstract: Primary neuroendocrine tumors of the fallopian tube are extremely rare with a few reported cases of high-grade neuroendocrine carcinoma and a single report of a carcinoid tumor arising in a teratoma. We report four cases of probable primary neuroendocrine tumors of the fallopian tube (two carcinoid tumors/ low-grade neuroendocrine tumors and two high-grade neuroendocrine carcinomas) in patients aged 49-71. These represent the first reported cases of primary tubal carcinoid tumor unassociated with a teratoma. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The majority of identified cases published, however, have no associated tumor and thus another possibility is that they arise from neuroendocrine cells in the fallopian tube. Grondin et al Pathology of the Lower 8 stained 16 normal fallopian tubes and found that 9 of these stained positive for chromogranin within mucosal epithelial cells, giving support to this theory. An alternative is that another tumor was present and was completely overgrown by the neuroendocrine component.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The majority of identified cases published, however, have no associated tumor and thus another possibility is that they arise from neuroendocrine cells in the fallopian tube. Grondin et al Pathology of the Lower 8 stained 16 normal fallopian tubes and found that 9 of these stained positive for chromogranin within mucosal epithelial cells, giving support to this theory. An alternative is that another tumor was present and was completely overgrown by the neuroendocrine component.…”
Section: Discussionmentioning
confidence: 93%
“…Of these, primary fallopian tube NENs are so rare that the latest WHO Classification of female genital tumors does not list them as a separate category (1). Only a handful of cases have been reported in the literature (3)(4)(5)(6)(7)(8)(9)(10). We report a unique case of grade 2 primary NET within the fallopian tube and examine its clinical presentation, review the literature, and discuss the challenges in diagnosis and therapeutic management.…”
mentioning
confidence: 97%
“…Neuroendocrine tumors are rare at all locations in the female genital tract (39). Tubal involvement of high-grade neuroendocrine carcinoma of gynecological origin has been mentioned in only a few reports in the literature (39,40). In a recent case report, primary ovarian large cell neuroendocrine carcinoma (LCNEC) secondarily spread to the tubal mucosa (39).…”
Section: Figure 3 Histological Features and Immunophenotype Of Tubal Intraepithelial Metastases From Small Cell Neuroendocrine Carcinoma mentioning
confidence: 99%
“…About two-thirds of NETs are GEP-NETs, mostly ariseing from the small intestine: small intestinal NETs are most frequently located in the distal ileum (4). On the other hand, as NE cells are distributed all around the body, there are many reports indicating diverse locations such as the sphenoid sinus (5), middle ear (6,7), renal pelvis (8), mediastinum (9), retroperitoneum (10), medulla spinalis (11), cavernous sinus (12), lymph nodes (13), fallopian tubes (14) and the parotid gland (15). NETs may be benign when small (usually <1 cm), but when malignant (representing less than 2% of gastrointestinal malignancies) they metastasise often before becoming symptomatic, generally when the tumour is larger than 2 cm.…”
Section: Epidemiology and Classificationmentioning
confidence: 99%